2021
DOI: 10.3389/fmars.2021.784586
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptome Analysis of Exogenous L-Arginine in the Alleviation of High-Temperature Stress in Gracilariopsis lemaneiformis

Abstract: Gracilariopsis lemaneiformis (G. lemaneiformis) is an important marine red macroalgae with high economic and ecological value all over the world. To date, global warming is a key issue that has a great impact on all living organisms, such as macroalgae. L-arginine (Arg) is a precursor of nitric oxide (NO) and polyamines (PAs), which can induce stress defense responses in land plants. However, its role in inducing algae resistance at high temperature (HT) is unclear. In this study, G. lemaneiformis thalli were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Since the PA synthetic gene GlSPDS markedly response to high temperature, we aimed to reveal the role of exogenous PA [spermidine (SPD) and spermine (SPM)] on G. lemaneiformis under high temperature. As our previous study indicated, RGR of G. lemaneiformis at 30/30°C was significantly decreased compared with 23/23°C (Zhang et al, 2021). In the present study, we first examined whether SPD and SPM could alleviate HT-induced growth decline of G. lemaneiformis.…”
Section: Relative Growth Ratementioning
confidence: 82%
See 1 more Smart Citation
“…Since the PA synthetic gene GlSPDS markedly response to high temperature, we aimed to reveal the role of exogenous PA [spermidine (SPD) and spermine (SPM)] on G. lemaneiformis under high temperature. As our previous study indicated, RGR of G. lemaneiformis at 30/30°C was significantly decreased compared with 23/23°C (Zhang et al, 2021). In the present study, we first examined whether SPD and SPM could alleviate HT-induced growth decline of G. lemaneiformis.…”
Section: Relative Growth Ratementioning
confidence: 82%
“…As is known, the wild G. lemaneiformis can growth prolifically under the temperature range of 10°C to 23°C, once beyond the upper limit its production may be reduced or even cease (Lv et al, 2019). Many studies showed high temperature (HT) stress could induce overaccumulation of reactive oxygen species (ROS) in algae, which oxidizes cellular components of lipids, proteins, and nucleic acids, and brings damage to cellmembranes (Zhang et al, 2020;Zhang et al, 2021). Under these circumstances, algae and plants may upregulate the activities of antioxidant enzymes to decrease the malondialdehyde (MDA) content and thereby reduce membrane damage (Mittler et al, 2004;Wang et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, heat stress could down-regulate energy metabolisms, decreasing the intermediate product of glycolysis and TCA cycle in the response of L. edodes to heat stress ( Zhao et al, 2019 ). Exogenous L-Arginine was reported to enrich the DEGs involved in glycolysis, TCA cycle, and oxidative phosphorylation in Gracilariopsis lemaneiformis under heat stress ( Zhang et al, 2021b ). In the present study, 2,4-D could remarkably enhance the energy metabolism by activating the expression of genes encoding the TCA cycle (e.g., pyruvate dehydrogenase, citrate synthase, phosphoenolpyruvate carboxykinase, and fumarate reductase) and electron transport chain NADH dehydrogenase, cytochrome c reductase, cytochrome c oxidase, and ATPase ( Figures 2B , 3 ) under thermal stress, it can provide energy for subsequent mycelial regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenously applied arginine significantly improves the tolerance against abiotic stress damages in various crops ( Nasibi et al., 2013 ; Karpets et al., 2018 ; Silveira et al., 2021 ). Similarly, arginine is significant in combating a non-conducive environment through arginine-derived stress-related substances under high-temperature stress in G. lemaneiformis ( Zhang et al., 2021 ) ( Figure 3 ).…”
Section: Polyamines and Abiotic Stressesmentioning
confidence: 99%
“… A model diagram for Arg-induced high temperature tolerance in G. lemaneiformis attributed to physiological and transcriptional alterations. PE, phycoerythrin; PC, phycocyanin; MDA, malondialdehyde; SOD, superoxide dismutase; APX, ascorbate peroxidase; TRX, thioredoxin; MDAR, monodehydroascorbate reductase; PRXR, peroxiredoxins; OAT, ornithine–oxo-acid transaminase; P5CR, pyrroline-5-carboxylate reductase; SAMDC, S-adenosylmethionine decarboxylase; GABA, γ-aminobutyric acid; PAO, polyamine oxidases; NAD+, aldehyde dehydrogenase; Asp, aspartate; His, histidine; Gly, glycine; Cys, cystine; Ser, serine; Thr, threonine; Val, valine; Ala, Alanine; PK, pyruvate kinase; PDH, pyruvate dehydrogenase; ENO, enolase; TCA, tricarboxylic acid; IDH, isocitrate dehydrogenase; CSY, citrate synthase; αKGDH, 2-oxoglutarate dehydrogenase ( Zhang et al., 2021 ). …”
Section: Polyamines and Abiotic Stressesmentioning
confidence: 99%